Determination of whole blood and plasma viscosity in term neonates by flow curve analysis with the LS300 viscometer 1 - Kuß, Navina; Bauknecht, Elisa; Schmidt, Claudia; Gehm, J.; Gehm, L.; Pöschl, Johannes; Ruef, Peter (Clinical hemorheology and microcirculation, 2016)
Determination of shear stresses at given shear rates allow approximation of flow curves by mathematical models and to calculate viscosities of non-Newtonian fluids. In term neonates, the mean arterial blood pressure (MAP) is markedly below that of adults, therefore rheological properties of blood play an important role in maintaining perfusion.
Gesehen am 03.06.2020